Economic forces on gold price in Malaysia / Faiqah Zulaikha Mohd Nasir ... [et al.] - Mohd Nasir, Faiqah Zulaikha; Wan Zakaria, Wan Mohd Farid; Musa, Mohd Hafizan; Burhanuddin, Muhammad Addin; Azman Ong, Mohd Hanafi (2018)
During the occurrence of a financial crisis, investors will take gold as an alternative to investment as gold is used as an instrument to hedge against inflation. To add, during an uncertain economic condition, investors will flock to the gold market as a protection against uncertainty. The factors specifically influencing the gold price are unknown before, during and after the financial crisis. The main objective of this research is to examine the relationship between macroeconomic factors with gold price before, during and after the financial crisis period in Malaysia. The period of the study encompasses a nine (9) year period starting from years2004 to 2006 as the period before the financial crisis, years 2007 to 2009 as the financial crisis period, and years 2010 to 2012 as the period after the financial crisis. This study is conducted on a monthly data basis. To measure the relationship between the macroeconomic factors and gold price, interest rates, exchange rates, inflation rates and crude oil prices have been selected as the independent variables. From this study, exchange rates are found to have a significant relationship with gold price in the three examined periods and the relationship is defined as an inverse relationship. As for after the financial crisis, inflation rates are found to have a positive significant relationship with gold price, while crude oil prices are found to have a significantly negative relationship with gold price.